(untitled) (Colombia Medica, 1993)
Fever is one of the most frequent causes of consultation in primary pediatric care. Its treatment includes a diversity of antipyretic drugs. A brief and detailed revision of the pharmacological properties and their main side effects, especially over the kidneys, of the most commonly used antipyretics is made.